Boganmeldelser - Mikael Rask Madsen; Hans Klette; Rune H. Scherg; Lars Holmberg; Peter Garde; Susanne Clausen; Roddy Nilsson; Hans Henrik Brydensholt; Jonas Havelund (Nordisk Tidsskrift for Kriminalvidenskab)
Book reviews